Elemental Composition of Various Apple Cultivars Grown in Serbia - S. Mitic, Snezana; N. Pavlovic, Aleksandra; B. Tosic, Snezana; T. Stojanovic, Branka; N. Mitic, Milan; B. Stojkovic, Milan (Asian Journal of Chemistry, 2013)
Metals are essential for important biochemical and physiological functions and are necessary for maintaining health throughout life. In order to assess the impact of human activity on the food chain, monitoring of trace metals in a apple samples has been focus of this study. Trace levels of metals such as Na, Mg, Ca, Co, Cr, Cu, Fe, Mn, Ni, Pb, Zn and Cd were determined in five different varieties of apples purchased from local market of Niš city of Serbia. Metal levels analyzed by using inductively coupled plasma optical emission spectrometry (ICP-OES). Among the 12 elements analyzed, sodium was the most abundant element distributed throughout all analyzed apple samples. Iron was the predominant minor element constituents. The accuracy of the results was evaluated by spike recovery tests. Analysis of variance was used to establish the metals with significant difference in mean content between the cultivars from apples.